Sex points : reclaim your sex life with the revolutionary multi-point system - Marcus, Bat Sheva (Go, Hachette Books, 2021)
Drawing on her twenty years of experience as a sex therapist, the author, in this refreshingly honest book, helps readers identify and analyze for themselves what factors are affecting their sex life by using the revolutionary Sex Points Assessment.